Improving the State of Automotive Software Engineering - Haghighatkhah, Alireza; Oivo, Markku; Banijamali, Ahmad; Kuvaja, Pasi (IEEE software, 2017)
The automotive industry is fundamentally changing by becoming software intensive, rather than mechanically intensive. To stay ahead of the game, automakers must continuously improve their software engineering. For this article, the authors studied the existing literature on the subject and made practitioner-oriented recommendations.